Characterizing internet health information seeking strategies by socioeconomic status: a mixed methods approach. Issue 1 (December 2016) - Perez, Susan; Kravitz, Richard; Bell, Robert; Chan, Man; Paterniti, Debora
Abstract Background The Internet is valuable for those with limited access to health care services because of its low cost and wealth of information. Our objectives were to investigate how the Internet is used to obtain health-related information and how individuals with differing socioeconomic resources navigate it when presented with a health decision. Methods Study participants were recruited from public settings and social service agencies. Participants listened to one of two clinical scenarios – consistent with influenza or bacterial meningitis – and then conducted an Internet search. Screen-capture video software captured the Internet search. Participant Internet search strategies were analyzed and coded for pre- and post-Internet search guess at diagnosis and information seeking patterns. Individuals who did not have a college degreeand were recruited from locations offering social services were categorized as "lower socioeconomic status" (SES); the remainder was categorized as "higher SES." Participants were 78 Internet health information seekers, ranging from 21–35 years of age, who experienced barriers to accessing health care services. Results Lower-SES individuals were more likely to use an intuitive, rather than deliberative, approach to Internet health information seeking. Lower- and higher-SES participants did not differ in the tendency to make diagnostic guesses based on Internet searches. Lower-SES participants were more likely than their higher-SES counterparts to narrow the scope of their search. Conclusions Our findings suggest that individuals with different levels of socioeconomic status vary in the heuristics and search patterns they rely upon to direct their searches. The influence and use of credible information in the process of making a decision is associated with education and prior experiences with healthcare services. Those with limited resources may be disadvantaged when turning to the Internet to make a health decision.